SECONDARY SCHOOL STUDENTS' METACOGNITIVE AWARENESS OF READING STRATEGIES IN ENGLISH AS A SECOND LANGUAGE - Arimbi Trian Hartanti; Abd. Rahman; Triana Kartika Santi; St. Shabibatul Rohmah (RADJA PUBLIKA, 2023)
Metacognitive awareness is considered a key factor for proficient strategic reading, particularly for academic reading. That this study was designed to determine high school students' metacognitive awareness about academic reading strategy. Thus, through the Reading Strategy Survey, Global students' metacognitive awareness, Problem Solving and the reading support strategies used in academic reading are investigated. The results show that the participants usually use academic reading strategies so they are often aware of these strategies. They mostly use and realize problem solving strategies but supporting strategies are least used in academic reading. This study uses a survey in data collection. To achieve the goal, 104 questionnaires were administered to all participants. Researchers use the average as a measure to determine the level of use category for each category of reading strategy. The survey questionnaire developed by Mokhtari and Sheorey (2002) is called Survey of Reading Strategies (SORS). The reading strategy here is based on the SORS questionnaire, namely global reading strategies, problem solving strategies, and supporting strategies. This study found that students' use of reading strategies was high with students' preference for problem solving strategies. Suggestions are made for English teachers who can help them to improve student learning better, such as for students to know about how to apply the reading strategies they use well, and also for future researchers who have similarities with this research.